United States Intervention Against Terrorism in Iraq - Ida Susilowati; Nur Rohim Yunus; Muhammad Sholeh (SALAM: Jurnal Sosial dan Budaya Syar-i, 2018)
Abstract: Terrorism is a crime committed by a group of people to frighten, terrorize, intimidate a country's government. In the case of the September 11, 2001 terror that occurred at the World Trade Center and the Pentagon, the United States accused the al-Qaeda group of being behind the attack. Furthermore, the United States attacked Afghanistan and Iraq. America considers the attacks carried out are legitimate because they are carried out to reduce world terrorism crimes. Whereas behind that there is another motive for controlling the oil in the country that it attacked.Keywords: Terrorism, Intervention, United States. Abstrak:Terorisme merupakan kejahatan yang dilakukan oleh sekelompok orang guna menakuti, meneror, mengintimidasi pemerintahan suatu negara. Dalam kasus teror 11 September 2001 yang terjadi pada World Trade Center dan Pentagon, Amerika Serikat menuduh kelompok al-qaidah di balik serangan tersebut. Selanjutnya Amerika Serikat melakukan penyerangan terhadap Afghanistan dan Iraq. Amerika menganggap serangan yang dilakukan adalah sah karena dilakukan untuk meredam kejahatan terorisme dunia. Padahal di balik itu ada motif lain untuk menguasai minyak yang ada di negara yang diserangnya.Kata Kunci: Terrorisme, Intervensi, Amerika Serikat